IE System in Modern Japanese Society - Rima Devi (Andalas International Journal of Socio-Humanities, 2023)
This paper explores the transformation of the traditional family system in Japanese society, known as the IE system, to a modern family structure influenced by Western ideologies. Historically, the Japanese state was conceptualized as a family state or kazokukokka, with the emperor as the head of the family, as seen in the Meiji Constitution. However, after Japan's defeat in World War II, the allied governments abolished this system, leading to gradual changes in the societal structure. The objective of this research is to investigate how Japanese people have adapted their family system from the traditional IE system to a modern one. The study utilizes a descriptive qualitative approach, employing field research reports and literature related to the contemporary Japanese family system. Data was collected and analyzed using descriptive methods to draw conclusions. The findings of the research highlight that while the IE system was officially removed from the Japanese Constitution, its influence persists in certain aspects of modern Japanese society. Scholars widely agree that remnants of the traditional family system still endure due to the lack of a viable replacement. Eradicating a deeply rooted cultural tradition developed over centuries proves to be a challenging task. This study sheds light on the coexistence of traditional and modern elements within the Japanese family system, presenting a nuanced understanding of how the IE system continues to partially shape family dynamics in contemporary Japanese society.